Folic Acid Supplementation of Female Mice, with or without Vitamin B-12, before and during Pregnancy and Lactation Programs Adiposity and Vascular Health in Adult Male Offspring. Issue 4 (9th March 2016) - Aleliunas, Rika E; Aljaadi, Abeer M; Laher, Ismail; Glier, Melissa B; Green, Tim J; Murphy, Melissa; Miller, Joshua W; Devlin, Angela M
Abstract: Background: The developmental origins of health and disease theory suggest that disturbances in the fetal and early postnatal environment contribute to chronic adulthood diseases, such as type 2 diabetes and cardiovascular disease. Greater adiposity and insulin resistance have been reported in children of women with high erythrocyte folate but poor vitamin B-12 status during pregnancy. The mechanisms underlying this relation are not known. Objective: The objective of this study was to investigate the effects of maternal supplemental folic acid, with or without vitamin B-12, on adiposity, glucose homeostasis, and vascular health in adult male offspring mice. Methods: Female C57BL/6J mice were fed a control diet (M-CON, 2 mg folic acid/kg, 50 μg vitamin B-12/kg) or a folic acid–supplemented diet with [10 mg folic acid/kg, 50 μg vitamin B-12/kg (SFA+B12)] or without [10 mg folic acid/kg, no vitamin B-12 (SFA-B12)] vitamin B-12 for 6 wk before mating and during pregnancy and lactation. The offspring were weaned onto a control diet (16% energy from fat) or a western diet (45% energy from fat) until 23 wk of age. The effects of maternal diet on adiposity, vascular function, and glucose tolerance were assessed in 6 groups of adult male offspring: control diet-fed M-CON, SFA+B12, and SFA-B12 and western diet-fed M-CON, SFA+B12, and SFA-B12. Results: Control and western diet-fed SFA-B12 and SFA+B12 offspring had smaller visceral and subcutaneous adipose tissue than M-CON offspring ( P < 0.05). Control SFA-B12 and SFA+B12 offspring had lower serum total adiponectin and vitamin B-12 concentrations and lower NADPH oxidase 2 expression in aorta compared with M-CON offspring ( P < 0.05). These effects were not observed in western diet-fed offspring. Conclusions: Folic acid supplementation of female mice before and during pregnancy and lactation, with or without dietary vitamin B-12, affects adult male offspring adiposity, vascular function, and one-carbon metabolism in those fed a control diet but not a western diet.